Lung parenchymal development in premature infants without bronchopulmonary dysplasia. Issue 12 (2nd December 2014) - Assaf, Santiago J.; Chang, Daniel V.; Tiller, Christina J.; Kisling, Jeffrey A.; Case, Jamie; Mund, Julie A.; Slaven, James E.; Yu, Zhangsheng; Ahlfeld, Shawn K.; Poindexter, Brenda; Haneline, Laura S.; Ingram, David A.; et al.
Summary: Rationale: While infants who are born extremely premature and develop bronchopulmonary dysplasia (BPD) have impaired alveolar development and decreased pulmonary diffusion (DLCO ), it remains unclear whether infants born less premature and do not develop BPD, healthy premature (HP), have impaired parenchymal development. In addition, there is increasing evidence that pro‐angiogenic cells are important for vascular development; however, there is little information on the relationship of pro‐angiogenic cells to lung growth and development in infants. Objective: and Methods Determine among healthy premature (HP) and fullterm (FT) infants, whether DLCO and alveolar volume (VA ) are related to gestational age at birth (GA), respiratory support during the neonatal period (mechanical ventilation [MV], supplemental oxygen [O2 ], continuous positive airway pressure [CPAP]), and pro‐angiogenic circulating hematopoietic stem/progenitor cells (CHSPCs). We measured DLCO, VA, and CHSPCs in infants between 3–33 months corrected‐ages; HP (mean GA = 31.7 wks; N = 48, ) and FT (mean GA = 39.3 wks; N = 88). Result: DLCO was significantly higher in HP than FT subjects, while there was no difference in VA, after adjusting for body length, gender, and race. DLCO and VA were not associated with GA, MV and O2 ; however, higher values were associated with higher CHSPCs, as well as treatment with CPAP. Conclusion: Our findings suggest that in the absence of extreme premature birth, as well as BPD, prematurity per se, does not impair lung parenchymal development.Pediatr Pulmonol. 2015; 50:1313–1319. © 2014 Wiley Periodicals, Inc.